Design, Synthesis and Biological Evaluation of Pyridin‐3‐yl pyrimidines as Potent Bcr‐Abl Inhibitors. (14th March 2014) - Pan, Xiaoyan; Dong, Jinyun; Gao, Hongping; Wang, Fang; Zhang, Yanmin; Wang, Sicen; Zhang, Jie
<x xml:space="preserve">Abstract</x> A series of pyridin‐3‐yl pyrimidines was synthesized and evaluated for their Bcr‐Abl inhibitory and anticancer activity. The preliminary results indicated that some compounds were promising anticancer agents. Compounds A2, A8, and A9 exhibited potent Bcr‐Abl inhibitory activity, suggesting that aniline containing halogen substituents might be important for biological activity. Molecular docking was carried out to investigate the binding mode of them with Bcr‐Abl. Details of synthesis and SAR studies of these compounds are described.